Formation of motivational-need sphere of future teachers in the process of teaching at a pedagogical institute (Pedagogy of Higher and Secondary Education, 2012)
Annyuk O. A. Formation of motivational-need sphere of future teachers in the process. of teaching at a pedagogical instituteThe article discusses the conditions of formation of the need-motivotional sphere of future teachers in the process of studying in the pedagogical institute.
Keywords: personality; active work; the formation of professionalism; the need-motivotional sphere of personalitу